Study of the Pore Water Pressure Development Characteristics of PHC Pipe Piles in Soft Soil Foundations - Zhaolin Jia; Han Wu; Shuaiqi He; Qixiang Zhao; Xiaoxu Zhang (Buildings, 2024)
When constructing hollow prestressed high-strength concrete (PHC) pipe piles in soft soil foundations, the generation and dissipation of pore water pressure can induce negative friction on the pile. This phenomenon increases the settlement of the pile foundation and, in severe cases, can lead to pile deflection and flotation. To further investigate the development characteristics of pore water pressure during PHC hollow pipe pile driving in soft soil, this study combined existing theories and numerical models to analyze the generation and influence areas of pore water pressure. Field tests were conducted at three different sites: an untreated site, a surcharge preloading site, and a site treated with cement mixing piles and well dewatering. These tests monitored and analyzed the horizontal and vertical development and behavior of pore water pressure during pile driving at each site. The results indicate that during the pile driving process, when the horizontal distance from the pile center is 3d and 9d, the peak values of the excess pore water pressure in the site treated with cement mixing piles and well dewatering are 117 kPa and 100 kPa. After pile driving is completed, they decrease to 50 kPa and 48 kPa, respectively. The peak values of excess pore water pressure in the surcharge preloading site are 122 kPa and 97 kPa, and after pile driving, they decreased to 80 kPa and 21 kPa, respectively. The peak values of excess pore water pressure in untreated sites are 140 kPa and 121 kPa; after pile driving, they decreased to 82 kPa and 60 kPa, respectively. Pore water pressure increases with the depth of pile driving and decreases with distance from the pile driving location. The peak pore water pressure and dissipation rate during construction were found to be higher at the untreated site compared to the other two sites. Therefore, during pile sinking in soft soil foundations, dewatering and driving drainage boards are effective methods for reducing pore water pressure and accelerating its dissipation. These findings provide a theoretical basis and technical support for ensuring the safety of engineering constructions.